2017
DOI: 10.1093/trstmh/trx045
|View full text |Cite
|
Sign up to set email alerts
|

The ecology and epidemiology of Ross River and Murray Valley encephalitis viruses in Western Australia: examples of One Health in Action

Abstract: Arboviruses are maintained and transmitted through an alternating biological cycle in arthropods and vertebrates, with largely incidental disease in humans and animals. As such, they provide excellent examples of One Health, as their health impact is inextricably linked to their vertebrate hosts, their arthropod vectors and the environment. Prevention and control requires a comprehensive understanding of these interactions, and how they may be effectively and safely modified. This review concentrates on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This is illustrated in the Ross River and Murray Valley in Western Australia, where the risk of infection appears to shift with both natural climatic patterns and human-made environmental manipulations; and for which Mackenzie and colleagues describe a robust architecture of monitoring climate, animal, and vector populations, water sources, and other ecological factors determining human risk in order to prevent outbreaks. 6 The shift away from viewing the host and pathogen in isolation, to understanding the crucible in which they live, increases complexity and requires a more integrative scientific method that we now refer to as One Health. In this context, Machalaba and colleagues report on an interdisciplinary collaboration investigating how best to evaluate the economic value of investing in One Health approaches to better control and prevent zoonotic infections.…”
mentioning
confidence: 99%
“…This is illustrated in the Ross River and Murray Valley in Western Australia, where the risk of infection appears to shift with both natural climatic patterns and human-made environmental manipulations; and for which Mackenzie and colleagues describe a robust architecture of monitoring climate, animal, and vector populations, water sources, and other ecological factors determining human risk in order to prevent outbreaks. 6 The shift away from viewing the host and pathogen in isolation, to understanding the crucible in which they live, increases complexity and requires a more integrative scientific method that we now refer to as One Health. In this context, Machalaba and colleagues report on an interdisciplinary collaboration investigating how best to evaluate the economic value of investing in One Health approaches to better control and prevent zoonotic infections.…”
mentioning
confidence: 99%
“…Indeed, climate and weather patterns are important factors in the occurrence of epidemics, which have become the focus of many modeling studies. For example, natural climatic and weather trends influenced RRV’s pattern of infection, especially hydrological features [125,259] and temperatures [260,261,262]; and a modeling study predicts that global warming might lead to the presence of MAYV across all of the Brazilian territory [263].…”
Section: Discussionmentioning
confidence: 99%
“…The investigations presented in the current paper are, in effect, examples of One Health in action. Indeed, a One Health approach has been successfully used to understand JEV transmission and to provide tools to combat epidemics [5], and it has been suggested that the employment of One Health strategies, particularly those concerned with improving coordination and collaboration across different disciplines and jurisdictions, are essential to planning and initiating interventions to mitigate risk and in improving prevention and control of mosquito-borne arboviruses [52].…”
Section: Discussionmentioning
confidence: 99%